Emily the criminal - Ford, John Patton ca. 20. Jh; Bierman, Jeff ca. 20. Jh; Halpern, Nathan ca. 20. Jh; Lee, Amanda Wing Yee ca. 20. Jh; Plaza, Aubrey 1984-; Rossi, Theo 1975-; Echikunwoke, Megalyn 1983- (Universal Studios, 2023)
"Emily is a talented artist who, due to a minor criminal record, resorts to insecure contract work delivering food while her friend from art school, Liz makes work trips to Portugal for photo shoots. Down on her luck and saddled with student debt, Emily gets involved in a dangerous credit card scam that pulls her deep into the criminal underworld of Los Angeles, ultimately leading to deadly consequences." [jpc.de]
Original: USA 2022
Bildformat 2.39:1
Keywords: Film; DVD-Video